Dietary fiber intake and pancreatic cancer risk: a meta-analysis of epidemiologic studies - Wang, Chun-Hui; Qiao, Chong; Wang, Ruo-Chen; Zhou, Wen-Ping (Scientific reports, 2015)
Evidence on the association between dietary fiber intake and pancreatic cancer risk has been controversial. Therefore, we carried out this meta-analysis to summarize available evidence from epidemiologic studies on this point. Relevant studies were identified by searching PubMed, Embase and Web of Science databases as well as by reviewing the rence lists of relevant articles. Random or fixed-effects model was used to calculate the summary risk estimates and 95% confidence intervals (CIs). This meta-analysis included one cohort and thirteen case-control studies which involving a total of 3287 subjects with pancreatic cancer. After summarizing the risk estimates of these studies, we yielded a significant association between dietary fiber intake and pancreatic cancer risk among case-control studies (odds ratio = 0.54; 95%CI = 0.44–0.67; I 2 = 41.4%; P = 0.043) but a non-significant result in cohort study (hazard ratio = 1.01; 95%CI = 0.59–1.74). Additionally, significant inverse associations were observed when we carried out the stratify analyses by the study characteristics and adjustment for potential confounders among case-control studies. Given only one cohort study included in the present meta-analysis, further prospective-designed studies should validate our findings and report more detail results, including those for subtypes of fiber, the risk estimates which corrected the impact of measurement errors and fully adjust for the potential confounders.